Differences of Microleakage Between Pit and Fissure Sealant Materials Composite Resin and RMGIC - Fatmawati, Dwi Warna Aju; Budirahardjo, Roedy; Wilfira, Mia (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
The shape of deep and narrow pits and fissures can be a place of retention for both bacteria and debris and if this condition is left untreated, it can develop into caries. Effective efforts are needed to prevent caries, one of which is the application of pit and fissure sealants. Composite resin and resin-modified glass ionomer cement (RMGIC) are materials that are used as pit and fissure sealants. Consumption of drinks with an acidic pH, such as fermented milk, is one of the causes of microleakage because it degrades the sealant material. This study aims to know the differences in microleakage between pit and fissure sealant materials, composite resin, and RMGIC after immersion in fermented milk drinks. The sample of this research was divided into 2 groups, namely group A as composite resin and group B as RMGIC. Each group used a sample of 10 elements of the maxillary 1st premolar, then soaked in fermented milk drink for 6 hours at 37oC, followed by immersion in 2% methylene blue for 4 hours, then penetration of 2% methylene blue was checked using the Beta 4.0.3 of Scion Image program. The average microleakage of group A was 0.761 mm, and that of group B was 2.178 mm. There were differences in microleakage from the pit and fissure sealant material composite resin, and RMGIC composite resin had lower microleakage rates than RMGIC materials.